The Effect of Abdominal Stretching Exercise Therapy on Dysmenorrhea Pain Intensity in Adolescent Girls - Marini, Gita; Priyantini, Diah; Sumara, Retno; Ghaliza, Galuh Mutia (Universitas Airlangga, 2025)
Introduction: Adolescence is referred to as a transitional period towards adulthood or puberty which is marked by the occurrence of the first menstruation (menarche). Menstruation experienced by adolescent girls mostly causes pain called dysmenorrhea, although this is normal due to the production of prostaglandins. Prostaglandins will stimulate the smooth muscles of the uterine wall to contract. The higher the prostaglandin levels, the stronger the contractions will be, and the pain will also be stronger. This study aims to analyze the effect of abdominal stretching exercise therapy on the intensity of dysmenorrhea pain in adolescent girls. Methods: The research design used was quantitative with a quasi-experimental research design, namely pre-post test with control group design. The population in this study were junior high school students, sampling using purpose sampling technique with a total sample of 66 respondents (33 intervention groups and 33 control groups) taken according to the inclusion and exclusion criteria. The independent variable of the study was the abdominal stretching exercise technique and the dependent variable was the intensity of dysmenorrhea pain. Abdominal stretching exercise therapy was given using standard operating procedures and pain intensity was measured using the Visual Analog Scale (VAS). Results: The research data were statistically tested using the Wilcoxon test with a significance level of p<0.05. The results of the study showed that there was a significant effect of abdominal stretching exercise techniques on the intensity of dysmenorrhea pain with a value of p=0.000 (p<0.05). Conclusion: Abdominal stretching exercise intervention is effective to be applied in solving pain problems in adolescent girls who experience dysmenorrhea. Future research should explore the long-term effects and sustainability of abdominal stretching exercises in managing dysmenorrhea among adolescent girls, including variations in frequency, intensity, and duration of the intervention.